2009
DOI: 10.1016/s1674-4799(09)60008-x
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion behavior of tempered dual-phase steel embedded in concrete

Abstract: Dual-phase (DP) steels with different martensite contents were obtained by appropriate heat treatment of an SAE1010 structural carbon steel, which was cheap and widely used in the construction industry. The corrosion behavior of DP steels in concrete was investigated under various tempering conditions. Intercritical annealing heat treatment was applied to the reinforcing steel to obtain DP steels with different contents of martensite. These DP steels were tempered at 200, 300, and 400°C for 45 min and then coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…It has been found that steel bars with higher residual stress will corrode at a higher rate [20,21]. In Bangladesh, both the atmospheric temperature and humidity are high.…”
Section: Resultsmentioning
confidence: 99%
“…It has been found that steel bars with higher residual stress will corrode at a higher rate [20,21]. In Bangladesh, both the atmospheric temperature and humidity are high.…”
Section: Resultsmentioning
confidence: 99%
“…The corrosion potential provides qualitative observations and probably points out the corrosion of steel embedded in concrete to a large extent. On the other hand, reliable quantitative data on the corrosion of steel embedded in concrete can be obtained by measuring the steel's resistance or current density [2,24].…”
Section: Results Of Corrosion Testsmentioning
confidence: 99%
“…Changes in corrosion potentials versus time were indicated in graphs in order to determine whether the steel was active or passive. Recommendations on evaluation of potential measurement results in ASTM C876 experiment method are stated in Table 5 [2,[24][25][26].…”
Section: Corrosion Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Where CR is average corrosion rate (mm/year), K is constant (8.76 x 10 4 ), W is weight lost by the specimen during the test (g), A is = total surface area of the test specimen (cm 2 ), T is duration of exposure (h) and D is density of the specimen material (g/cm 3 ).…”
Section: Methodsmentioning
confidence: 99%